P2P Workspace / Sheik Azhar Bux Sheik Azmi Bux - Sheik Azhar Bux, Sheik Azmi Bux (2004)
P2P Workspace is a workspace where users can communicate with each other while doing several task in the workspace with a Peer-to-Peer (P2P) technology or communication. P2P Workspace is designed mainly to fulfill the requirements on the user needs of a workspace application. The workspace is designed to curb certain situation like to gather all the information for the users in a workspace, to ease people task, to allow adhoc connectivity as well as because of the increasing of decentralized individuals or group. The workspace will be for the use of all users who need the services such as file sharing, chatting, shared whiteboard, shared calendar and auto discovery. The implementation of P2P technology is due to the fact that P2P has given a lot of advantages to users to control and manage the use of files and data across networks.